2016
DOI: 10.1017/cem.2016.4
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacoeconomic study of traditional anticoagulation versus direct oral anticoagulation for the treatment of venous thromboembolism in the emergency department

Abstract: Objectives: Patients with venous thromboembolism (VTE) (deep vein thrombosis [DVT] and pulmonary embolism [PE]) are commonly treated as outpatients. Traditionally, patients are anticoagulated with low-molecular-weight heparin (LMWH) and warfarin, resulting in return visits to the ED. The direct oral anticoagulant (DOAC) medications do not require therapeutic monitoring or repeat visits; however, they are more expensive. This study compared health costs, from the hospital and patient perspectives, between trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…All of them suggested that DOACs are costeffective relative to VKA. 100,[104][105][106][107][108][109][110][111][112][113][114][115][116] Finally, we considered DOACs to be acceptable and feasible to implement in most scenarios. However, given their cost, some patients might not be able to afford them.…”
Section: Other Etd Criteria and Considerationsmentioning
confidence: 99%
“…All of them suggested that DOACs are costeffective relative to VKA. 100,[104][105][106][107][108][109][110][111][112][113][114][115][116] Finally, we considered DOACs to be acceptable and feasible to implement in most scenarios. However, given their cost, some patients might not be able to afford them.…”
Section: Other Etd Criteria and Considerationsmentioning
confidence: 99%
“…12 Frequent blood monitoring imposes a burden on the patient and healthcare system. 13 DOACs, which have been available in Canada since 2010, require no such routine monitoring and are given as fixed doses based on patient characteristics. Multiple studies, including phase 3 RCTs [14][15][16][17] and observational studies, 18 have thus contrasted the effectiveness (stroke and mortality prevention) and safety (risk of bleeding) of DOACs vs the mainstay warfarin for patients with atrial fibrillation.…”
Section: Comparing the Safety And Effectiveness Of Doacs Vs Warfarinmentioning
confidence: 99%
“…While the safety and effectiveness of warfarin are well understood, the level of anticoagulation achieved for patients on warfarin requires close monitoring of International Normalized Ratio (INR) and frequent dose adjustments due to numerous drug interactions 12 . Frequent blood monitoring imposes a burden on the patient and healthcare system 13 . DOACs, which have been available in Canada since 2010, require no such routine monitoring and are given as fixed doses based on patient characteristics.…”
Section: Comparing the Safety And Effectiveness Of Doacs Vs Warfarinmentioning
confidence: 99%
“…Vitamin-K antagonists remain the most widely used anticoagulation drug in the ED, although improving evidence suggests that DOACs are more viable and cost effective than conventional anticoagulation among acute VTE patients. 12,13 Several studies have been conducted to investigate the prescription of anticoagulants in VTE patients to obtain an extensive understanding of this gap between medical recommendations and clinical practice. 14,15 However, little is known concerning the trend in anticoagulant prescription for ED patients with VTE.…”
Section: Introductionmentioning
confidence: 99%